'Candidatus Adiutrix intracellularis', an endosymbiont of termite gut flagellates, is the first representative of a deep‐branching clade of Deltaproteobacteria and a putative homoacetogen. (21st April 2016) - Ikeda‐Ohtsubo, Wakako; Strassert, Jürgen F. H.; Köhler, Tim; Mikaelyan, Aram; Gregor, Ivan; McHardy, Alice C.; Tringe, Susannah Green; Hugenholtz, Phil; Radek, Renate; Brune, Andreas
Summary: Termite gut flagellates are typically colonized by specific bacterial symbionts. Here we describe the phylogeny, ultrastructure and subcellular location of ' Candidatus Adiutrix intracellularis', an intracellular symbiont of Trichonympha collaris in the termite Zootermopsis nevadensis . It represents a novel, deep‐branching clade of uncultured Deltaproteobacteria widely distributed in intestinal tracts of termites and cockroaches. Fluorescence in situ hybridization and transmission electron microscopy localized the endosymbiont near hydrogenosomes in the posterior part and near the ectosymbiont ' Candidatus Desulfovibrio trichonymphae' in the anterior part of the host cell. The draft genome of ' Ca . Adiutrix intracellularis' obtained from a metagenomic library revealed the presence of a complete gene set encoding the Wood–Ljungdahl pathway, including two homologs of fdhF encoding hydrogenase‐linked formate dehydrogenases (FDHH ) and all other components of the recently described hydrogen‐dependent carbon dioxide reductase (HDCR) complex, which substantiates previous claims that the symbiont is capable of reductive acetogenesis from CO2 and H2 . The close phylogenetic relationship between the HDCR components and their homologs in homoacetogenic Firmicutes and Spirochaetes suggests that the deltaproteobacterium acquired the capacity for homoacetogenesis via lateral gene transfer. The presence of genes for nitrogen fixation and the biosynthesis of amino acids and cofactors indicate the nutritional nature of the symbiosis.